2014
DOI: 10.1186/1475-2875-13-162
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care visit attendance, intermittent preventive treatment during pregnancy (IPTp) and malaria parasitaemia at delivery

Abstract: BackgroundThe determinants and barriers for delivery and uptake of IPTp vary with different regions in sub-Saharan Africa. This study evaluated the determinants of ANC clinic attendance and IPTp-SP uptake among parturient women from Mount Cameroon Area and hypothesized that time of first ANC clinic attendance could influence uptake of IPTp-SP/dosage and consequently malaria parasite infection status at delivery.MethodsTwo cross sectional surveys were carried out at the Government Medical Centre in the Mutengen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 29 publications
11
49
3
Order By: Relevance
“…Other results in this study revealed that though attendees at the ANCs were high, only very few of them actually got the IPT treatment, hence, a good number of the respondents sought for alternative means during malaria infection. This still concurred with findings of a study [39] which reported that treatment of illness in Nigeria usually commences in the household with self-medication. This could be due to low perceived benefits in a particular source of treatment or perceived threat about the illness itself.…”
Section: Discussionsupporting
confidence: 79%
“…Other results in this study revealed that though attendees at the ANCs were high, only very few of them actually got the IPT treatment, hence, a good number of the respondents sought for alternative means during malaria infection. This still concurred with findings of a study [39] which reported that treatment of illness in Nigeria usually commences in the household with self-medication. This could be due to low perceived benefits in a particular source of treatment or perceived threat about the illness itself.…”
Section: Discussionsupporting
confidence: 79%
“…This is an important point to be considered in every pregnancy women and as usually in high proportion of them receiving SP very late during their antenatal booking [26][27][28][29][30][31][32][33][34][35][36]. These practices were significantly associated with poor pregnancy outcome regarding intermittent presumptive treatment against malaria in pregnancy during antenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Cameroon transitioned from a 2-dose to a 3-dose recommendation for IPTp-SP in 2012 [33]. Monitoring studies on the coverage and usage of lPTp-SP and ITN (insecticide-treated nets) in pregnancy in the study area showed that the proportion of women who receive at least two or more doses of IPTp-SP (64%) has increased over the years [30,34] but levels remain below recommended target (80-100%). Also, recent findings confirm the additional benefits of repeated doses of SP in combination with ITN use in reducing peripheral malaria parasitaemia and maternal anaemia [30].…”
Section: Study Areamentioning
confidence: 99%